California Elected Women's Association for Education and Research Agenda (1977)
This document contains the agenda, budget reports, membership updates, and board meeting minutes for the California Elected Women's Association for Education and Research (CEWAER) in mid-1977. It details financial activity, proposed budget amendments, growth in membership (over 400 members with more than 100 new since May), and plans for regional development, conferences, newsletters, and directories. The minutes reflect active organizational planning around affirmative action, ERA support, collaboration with the Governor's Conference and League of Cities, travel reimbursement policies, and preparation for the May 1978 annual conference.